The perceived experience of students becoming positive change agents: A case of the Honors Living-Learning community program at Rutgers University - Newark - Plessis, Davy Julian Du; Hill, Macsu; Santana, Engelbert (American Journal of Social Sciences and Humanities, 2023)
Studies have found that in higher education institutions in the United States of America, a variety of resources, student engagement, institutional practices, and other stakeholders contribute to students’ perceptions of becoming positive change agents. This project explores how the Honors Living-Learning Community (HLLC) program at Rutgers University-Newark (RUN), New Jersey capitalizes on resources, leadership, curriculum, and other strategies to promote students' perception to become positive change agents. Secondary research from a survey completed by the HLLC graduates was utilized for this project. As a descriptive study, survey responses were coded and evaluated to determine the HLLC’s impact on students’ perception on becoming positive change agents. The study found that the HLLC program at RUN successfully promotes students' perception to become positive change agents. The HLLC program achieves this through its curricular structure, which integrates academic rigor with community engagement, and a strong emphasis on leadership development. The HLLC’s success in developing positive change agents has practical implications for institutions of higher education. Other universities could consider replicating the HLLC 's unique curricular structure and community engagement strategies to promote leadership development and cultivate positive change agents among their graduates.